GSKJ4 Protects Mice Against Early Sepsis via Reducing Proinflammatory Factors and Up-Regulating MiR-146a - Pan, Yuchen; Wang, Jiali; Xue, Yaxian; Zhao, Jiaojiao; Li, Dan; Zhang, Shaolong; Li, Kuanyu; Hou, Yayi; Fan, Hongye (Frontiers in Immunology, 2018)
Sepsis, defined as life-threatening organ dysfunction, is one of the most common causes of mortality in intensive care units with limited therapeutic options. However, the mechanism underlying the regulation of epigenetics on sepsis remains largely undefined. Here we showed that JMJD3, the histone lysine demethylase, played a critical role in the epigenetic regulation of innate immunity during early sepsis. Pharmacological inhibition of JMJD3 by GSKJ4 protects mice against early septic death and reduced pro-inflammatory cytokine interleukin-1β (IL-1β) production as well as IL-6, tumor necrosis factor-α (TNF-α) and monocyte chemotactic protein-1 (MCP-1) expression. Interestingly, GSKJ4 up-regulated the transcription of anti-inflammatory microRNA-146a (miR-146a) in peritoneal macrophages from septic mice. Mechanistically, JMJD3 negatively regulated the transcription of miR-146a via its demethylation of H3K27me3 on the promoter of miR-146a. Moreover, the transcription of miR-146a was positively regulated by nuclear factor-κB (NF-κB) p65. Inhibition of NF-κB p65 promoted JMJD3 binding to miR-146a promoter and decreased the tri-methylation level of H3K27, while the inhibition of JMJD3 did not affect the recruitment of NF-κB p65 to miR-146a promoter. These results highlight an epigenetic mechanism by which JMJD3 was inhibited by NF-κB p65 from binding to miR-146a promoter to promote the anti-inflammatory response. Taken together, our findings uncover a key role for JMJD3 in modulating the miR-146a transcription and shed light on the JMJD3 inhibitors could be potential therapeutic agents for early sepsis therapy.